2019
DOI: 10.1111/pbr.12789
|View full text |Cite
|
Sign up to set email alerts
|

Delineating Genotype × Environment interactions towards durable resistance in mungbean against Cercospora leaf spot (Cercospora canescens) using GGE biplot

Abstract: Cercospora leaf spot (Cercospora canescens) is a major fungal disease which impedes mungbean production worldwide. Presence of wider host range with existence of pathogenic variability creates intricacy towards host‐pathogen dynamics. Moreover, environmental factors having crucial role in augmenting severity of this disease further complicate disease management. An attempt has been made for unfolding genotype x environment interactions towards identifying and validating durable resistant genotypes against cerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 41 publications
(72 reference statements)
4
8
0
Order By: Relevance
“…Among all the tested traits except for grain Ca, COI was observed for all the traits. Therefore, it can be said that within the same data set, both COI and non-COI were detected which was in affirmation with earlier findings ( Dehghani et al, 2006 ; Sabaghnia et al, 2008 ; Das et al, 2019 , 2020 ; Singh B. et al, 2020 ). The identified genotypes (G-75, G-76, G-60, G-27, G-95) for all the five studied traits would be precious genetic stocks for utilization as parents in a V. stipulacea biofortification program.…”
Section: Discussionsupporting
confidence: 89%
“…Among all the tested traits except for grain Ca, COI was observed for all the traits. Therefore, it can be said that within the same data set, both COI and non-COI were detected which was in affirmation with earlier findings ( Dehghani et al, 2006 ; Sabaghnia et al, 2008 ; Das et al, 2019 , 2020 ; Singh B. et al, 2020 ). The identified genotypes (G-75, G-76, G-60, G-27, G-95) for all the five studied traits would be precious genetic stocks for utilization as parents in a V. stipulacea biofortification program.…”
Section: Discussionsupporting
confidence: 89%
“…For each trait under study there was differential response of the genotype to environmental changes. Presence of significant environment × genotype interaction in response to disease resistance in our study was in accordance with the previously reported works on barley/net blotch interaction studied by Cherif et al (2010) as well as recent works on pea/leaf rust interaction studied by Das et al, (2019) as well as mung bean/ CLS interaction studied by Das et al, (2020).…”
Section: Genotype × Environment Interactionsupporting
confidence: 93%
“…Bootstrapping at 95% CL improved the precision of recommendation of a testing location and ME delineation. However, reported groupings of environments need to be further reconfirmed using multi-location testing data over more number of years as also reported by earlier authors (Yan et al, 2000;Silva et al, 2011;Phuke et al, 2017;Sánchez-Martín et al, 2017;Das et al, 2020). Also, the performance and stability of all selected materials advocate additional testing in central and southern pearl millet-growing regions of the country for the future development of elite FB-resistant cultivars.…”
Section: Discussionmentioning
confidence: 66%